Nascimento por cesariana e adiposidade central em adolescentes de uma coorte de nascimentos (RPS) de uma capital do nordeste brasileiro - ABREU, Joana D’Arc Matos França de (2018)
INTRODUCTION: Caesarean section has been associated with the development of obesity and metabolic changes throughout life, but studies on the association with central fat, more associated with cardiovascular risk, are not consensual. OBJECTIVE: To evaluate the causal effect between cesarean birth and central adiposity of the body in adolescents. METHODS: A cohort study was carried out, including 601 participants, evaluated at birth and in adolescence aged 17 to 18 years. The following ratios were evaluated by DEXA as the definition of central fat: android / gynoid fat mass (A/G); trunk / total fat mass (T/T); fat mass of the trunk / limbs (T/LB) and fat mass of the trunk / legs (T/LG). A Directed Acyclic Graph (DAG) was constructed to select the variables for minimum adjustment for confounding, being selected: intrauterine growth retardation, gestational age at birth, maternal schooling, maternal smoking, mother's BMI, family income at birth and the mother's marital status. In the analysis, a marginal structural model was used, which allows a better adjustment of the confounders. We also used inverse-weighted estimators of the likelihood of exposure selection. The presence of interchangeability between the exposure groups was verified by the teballance command of the software StataTM v. 14. RESULTS: There was no statistical difference in the central fat mass of adolescents born by cesarean section or vaginal route, for the four indicators used: A/G ratios (CI 95% = -0.015, 0.018, P = 0.875); T/T ratio (CI 95% = -0.013; 0.007, P = 0.541); T/LB ratio (CI 95% = -0.048; 0.016; P = .333); T/LG ratio (CI 95% = -0.06; 0.03, P = 0.532). CONCLUSION: In the present study, no causal effect was observed between cesarean births and the higher presence of central fat in the adolescents studied.